ANIMAL ABUSE AND COLONIAL OPPRESSION IN PREMCHAND’S SHORT STORIES: A POSTCOLONIAL READING - Sharma, Shalini; Kumar, Sunil (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Munshi Premchand, one of the most prominent authors of early 20th-century Hindi and Urdu literature, often used animals as protagonists in his short stories. These figures are not just illustrative characters but also symbolic beings in the social, moral, and political structures. His stories protrayed how animals are subjected to neglect, exploitation, physical violence, and emotional abandonment, imitating substantial systems of domination in colonial India. This article investigates short stories such as Kutte ki Kahani, Do Bailon ki Katha, Sailani Bandar, Gubbare Par Cheetah, and Sher aur Ladka to discuss that Premchand’s representation of animal suffering can be interpreted as a literary reflection of colonial abuse and the dehumanization of India’s vulnerable classes. Through a postcolonial and antrozoological lens, the article demonstrates that animal characters in Premchand become areas where power, violence, and resistance are performed, coresponding the experience of colonized Indian subjects under British imperial rule.